Construction and Optimizing Domain Driven Design Principles and Twelve Factor Application Methodology for Software Backend Architecture - Kurniawan, Risky; Sanjaya, Rangga (International Journal Labs, 2025)
Abstract—Software architecture plays a crucial role in software development; however, finding an architecture that remains continuously adaptable, employs a declarative format, supports scaling, and is suitable for modern cloud platforms is challenging. Additional challenges often arise due to business and technical obstacles during development. This study aims to design a software architecture that supports continuous development, enables declarative deployment, and incorporates clean contracts based on the twelve-factor app methodology. The goal is to create an architecture that applies to modern cloud platforms, supports scalability, and leverages domain-driven design to eliminate business and technical constraints. The research follows a waterfall methodology, starting with analysis, followed by system design, implementation, testing, and delivery. The findings indicate that the proposed architecture exhibits continuous development characteristics and adopts the twelve-factor app principles, resulting in a descriptive format and clean contracts. The architecture is also compatible with modern cloud platforms and allows for scaling. Additionally, the use of domain-driven design enhances the effectiveness of resource allocation and helps to eliminate business and technical limitations.